Peningkatan Minat Dan Bakat Melalui Pentas Seni Pada Siswa Sekolah Dasar - Marlin Chrisye Wattimena; Ronald Darlly Hukubun; Eva S. Ratuluhain; Emilia Hanubun; Murad Madi (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
Art performance activities as a form of community service by the Pattimura University KKN student program, Batch L in Tihu Village, collaborated with SD Negeri 46 and SD Negeri 56 Perumnas Poka. The purpose of this activity is to increase self-confidence, as well as explore and hone students' requests and talents for various arts and cultures. The results of the implementation of this art performance activity show that students of SD Negeri 46 and SD Negeri 56 Perumnas Poka have diverse talents, this activity provides a forum for students to channel their interests and talents, increase their creativity and innovation in the fields of poetry reading, speeches, solo singing and group singing, as well as fostering a sense of togetherness and kinship between students of SD Negeri 46 and SD Negeri 56 Perumnas Poka.